THE EFFECT OF PERCIEVE USEFULLNESS, SELF-EFFICASY AND PERCIEVE EASE OF USE TOWARD INTENTION TO USE ONLINE SHOPPING APLICATION (The Empirical Study of The Brand Lazada Indonesia in Pontianak) - Al-Haq, Al-Haq Asri B1024131012 (Jurnal Manajemen Update, 2018)
The study investigated the effects of perceived ease of use, sefl-efficacy, company credibility and perceived usefulness toward intention to use. Moreover, the direct and indirect effects of values and involvement on intention to use were studied. The study utilized the survey questionnaire and Lazada online shopping aplication as the product being researched. The sample consisted of 100 respondent who responded to an anonymous questionnaire. Five hypotheses were tested and four of them were confirmed by the data. Using statistical software (Smart PLS) hypothesis shows that these variables have positive and negative significant relationship. Practical contribution shows that this study can be used as a guideline to management and marketers to improve the product quality. The results of the study provide several theoretical and practical implications.Â Keywords: perceived ease of use, self-efficacy, company credibility, perceived usefulness, intention to use, lazadaÂ